PROBLEMS IN THE PROCESS OF FORMING THE COMPOSITION OF INDUSTRIAL WORKERS AND STAFF TRAINING IN UZBEKISTAN IN 1925-1940 (IN THE EXAMPLE OF THE SOUTHERN REGIONS) - Mamatqulov B. S. (TARIXIY TADQIQOTLAR, 2025)
In this article, the issue of forming the structure of industrial workers in Uzbekistan and providing enterprises with personnel, conflicting situations in the process of training industrial personnel are analyzed historically on the basis of scientific sources.